2016
DOI: 10.3892/etm.2016.3909
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the MAPK pathway and the expression of CAR in a murine model of viral myocarditis

Abstract: The pathogenesis of viral myocarditis (VMC) is not fully understood. This study aimed to examine the relationship between coxsackie-adenovirus receptor (CAR) and the p38 mitogen activated protein kinase (MAPK) pathway mechanisms in a mouse model. Three groups of mice were established: 5 mice in a control group injected with saline, 15 in the model group injected with coxsackie virus B3 (CVB) and 15 in the intervention group injected with CVB3 but treated with the p38 MAPK inhibitor SB203580. Mice were sacrific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…Nakao et al demonstrated that LIPUS affected the inflammatory responses of osteoblasts to LPS, where LPS‐induced production of inflammatory cytokines and phosphorylation of ERK and p38MAPK were decreased by LIPUS treatment . In addition, recent studies indicated that p38 MAPK and ERK signallings played pivotal roles in the pathogenesis of viral myocarditis, and suppressing these signallings led to an inhibition of cardiac injury and benefited the recovery from viral myocarditis . In our study, we also found that p38 MAPK and ERK signallings were activated during viral myocarditis, while LIPUS treatment suppressed these signallings and attenuated the excessive inflammatory response during the disease course.…”
Section: Discussionsupporting
confidence: 78%
“…Nakao et al demonstrated that LIPUS affected the inflammatory responses of osteoblasts to LPS, where LPS‐induced production of inflammatory cytokines and phosphorylation of ERK and p38MAPK were decreased by LIPUS treatment . In addition, recent studies indicated that p38 MAPK and ERK signallings played pivotal roles in the pathogenesis of viral myocarditis, and suppressing these signallings led to an inhibition of cardiac injury and benefited the recovery from viral myocarditis . In our study, we also found that p38 MAPK and ERK signallings were activated during viral myocarditis, while LIPUS treatment suppressed these signallings and attenuated the excessive inflammatory response during the disease course.…”
Section: Discussionsupporting
confidence: 78%
“…Circ 0071542 was predicted to regulate the expression of MAPK by binding hsa-miR-8055. A number of scholars have demonstrated that MAPK participates in the development of myocarditis [38][39][40]. Thus, we speculated that circ 0071542 has a proinflammatory function in fulminant myocarditis by sponging miR-8055 to control MAPK expression.…”
Section: Discussionmentioning
confidence: 94%
“…The PI3K/AKT and p38 MAPK signaling pathways are critical in cell survival and can be activated by multiple viruses ( Cheng et al, 2020 ; Zhan et al, 2020 ), including rotavirus, varicella-zoster virus (VZV), HIV-1, HSV-1, coxsackievirus B3 (CVB3), Epstein–Barr virus (EBV), severe acute respiratory syndrome (SARS) coronavirus, and hepatitis B virus/hepatitis C virus (HBV/HCV) ( Rahaus et al, 2004 ; Lobeck et al, 2016 ; Niu et al, 2017 ; Zhang et al, 2018 ; Torresi et al, 2019 ; Wang et al, 2019 ; Bouhaddou et al, 2020 ). Activated PI3K/AKT and p38 MAPK can mediate apoptosis, cell differentiation, growth, or immune responses ( Cooray, 2004 ; Sun et al, 2015 ), among which evasion of cell cycle checkpoint regulation and apoptosis inhibition are the major pathways to maintain cell survival and HSV-1 reproduction ( Fehr and Yu, 2013 ; Banerjee et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%